Giant Inflammatory Polyposis of the Rectum as a Complication of Ulcerative Colitis - Theeran Gill; Jaikumar Nallamuthu; Shabbar Husain; Wazir Azzam; Mohd Firdaus Mohd Hayati; Ismail Sagap (Surgical Society of Kenya, 2022)
Inflammatory bowel disease is an emerging gastrointestinal disease in Malaysia. One of its rare complications includes giant inflammatory polyposis (GIP). A 39-year-old woman presented with worsening per rectal mucous discharge, associated with blood, colicky abdominal pain, and weight loss. A series of endoscopies at another hospital did not provide an inconclusive diagnosis. Another repeat colonoscopy showed a left-sided colitis with marked erythema and friability with islands of polyps; this was concluded to be an ulcerative colitis based on histopathology; thus, medical treatment was commenced. However, 2 months later, the patient presented with constipation, which required laxatives, as well as a worsened lower abdominal pain. Subsequent colonoscopy revealed obstruction-caused GIP at the mid rectum extending to the lower rectum, which was confirmed by imaging modalities. She was diagnosed with obstructing GIP coupled with ulcerative colitis, and panproctocolectomy and ileal pouch anal anastomosis were planned.